Assistance of Madiun City Political Party Managers in Compiling Accountability Reports on the Use of Political Party Financial Aid Funds - Elly Astuti; Nurharibnu Wibisono (Engagement: Jurnal Pengabdian Kepada Masyarakat, 2021)
Finance is one of the important aspects in determining the sustainability and credibility of political parties, and will indirectly affect the political quality of a country. For this reason, transparency in the financial management of political parties is required in accordance with applicable regulations. However, some cadres of political party administrators in the regions have difficulty in compiling accountability reports because they do not have an educational background in accounting. For this reason, assistance is needed to compile a simple accountability report with the help of a general cash book that is easy to understand and practical. The results of the activity showed that the preparation of the general ledger was able to increase participants' understanding of the procedures for preparing accountability reports more easily even though they did not previously have basic knowledge of accounting.